Pengembangan Instrumen Sikap Nasionalis Pada Peserta Didik Sekolah Dasar - Eni Rahmawati (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2023)
This research aims to develop alternative instruments to assess the nationalist attitudes of learners in elementary schools. The method in this research is R&D model. The sample was chosen by purposive sampling with research subjects of high grade students in elementary school. Instruments in this study using a modified Likert Scale. The validity test used is content validity and construct validity. Content validity is measured using CVR (Content Validity Ratio) and construct validity is measured using EFA (Exploratory Factor Analysis). Testing the validity of the constructs extracts the components into eight, namely (1) Prioritizing the public interest above personal interests, (2) the spirit of sacrificing, (3) Unity and unity of the nation, (4) Patriotik in maintaining and promoting the nation, (5) Respect and preserve national culture, (6) cooperate, (7) tolerance, and (8) peace love). Test Reliability using Alpha Cronbach with good category. The nationalist attitude assessment instrument is feasible to use and can be developed by the teacher according to the specified grid.